Implementation of Imla Method in Mahārah al-Kitābah Learning to Students’IX Class MTsNU Nurul-Huda Mangkang Semarang: Taṭbīq Tarīqah al-Imla’ li at-Ta’limi Mahārah al-Kitābah Lada Ṭullābu ash-Shaffi at-Tāsi’u MtsNU Nurul-Huda Mangkang Semarang - Ummu Zahrotun Ni'mah; Inayah Inayah; Ismail Ismail; Ikhrom Ikhrom (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2025)
The Imla method (IM) is a classical learning method that has the potential to be developed in the context of contemporary Arabic language learning (ALL). This is supported by the need for orthography in ALL and the basis for teaching writing skills (WS). This study aims to explore the implementation of the IM in learning maharah-kitabah Class IX MTs-NU Nurul-Huda Mangkang-Semarang; and analyze the supporting and inhibiting factors. This research uses a qualitative approach of explanatory descriptive method. The research sample was 35 ninth-grade students who were studying theme 4. Data analysis used Spradley's model, including four stages, domain, taxonomy, component, and cultural-theme analysis. The results showed the implementation stages of the IM include: teacher writes sentences, reads, and asks students to follow him. They are asked to pay attention, read, and remember the writing before it is erased, and write it back in the books. Thus, founded aspects of WS, namely spelling-accuracy, grammatical-understanding, ability to form-sentences, vocabulary-mastery, as well as student motivation and activeness. Supporting factors include the use of appropriate media, teachers mastering language skills, and teachers being able to choose appropriate methods. The inhibiting factors include lack of interest, limited time, lack of infrastructure, and unsupportive environment. Keywords: Arabic Learning, ALL, Dictation, Imla Method, Orthography, Writing Ability, Writing Skill, Transferred Dictation,